STIM2 Mediates Excessive Store-Operated Calcium Entry in Patient-Specific iPSC-Derived Neurons Modeling a Juvenile Form of Huntington's Disease - Vigont, Vladimir A.; Grekhnev, Dmitriy A.; Lebedeva, Olga S.; Gusev, Konstantin O.; Volovikov, Egor A.; Skopin, Anton Yu.; Bogomazova, Alexandra N.; Shuvalova, Lilia D.; Zubkova, Olga A.; Khomyakova, Ekaterina A.; Glushankova, Lyubov N.; Klyushnikov, Sergey A.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Huntington’s disease (HD) is a severe autosomal-dominant neurodegenerative disorder caused by a mutation within a gene, encoding huntingtin protein. Here we have used the induced pluripotent stem cell technology to produce patient-specific terminally differentiated GABA-ergic medium spiny neurons modeling a juvenile form of HD (HD76). We have shown that calcium signaling is dramatically disturbed in HD76 neurons, specifically demonstrating higher levels of store-operated and voltage-gated calcium uptakes. However, comparing the HD76 neurons with the previously described low-repeat HD models, we have demonstrated that the severity of calcium signaling alterations does not depend on the length of the polyglutamine tract of the mutant huntingtin. Here we have also observed greater expression of huntingtin and an activator of store-operated calcium channels STIM2 in HD76 neurons. Since shRNA-mediated suppression of STIM2 decreased store-operated calcium uptake, we have speculated that high expression of STIM2 underlies the excessive entry through store-operated calcium channels in HD pathology. Moreover, a previously described potential anti-HD drug EVP4593 has been found to attenuate high levels of both huntingtin and STIM2 that may contribute to its neuroprotective effect. Our results are fully supportive in favor of the crucial role of calcium signaling deregulation in the HD pathogenesis and indicate that the cornerstone of excessive calcium uptake in HD-specific neurons is a calcium sensor and store-operated calcium channels activator STIM2, which should become a molecular target for medical treatment and novel neuroprotective drug development.